PECULIARITIES OF COACHING AS A MODERN METHOD OF PERSONNEL MANAGEMENT AT THE ENTERPRISE - LEPEYKO, Tetiana; PERERVA, Ivanna; MATSIKANYCH, Daryna; SHEVCHENKO, Stanislav (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores coaching as a modern method of personnel management, particularly its role in employee development and increasing companies' competitiveness. Personnel is a key resource of any organization, so continuous development is essential for achieving strategic goals. In today's business environment, coaching is an important tool for improving professional skills, motivation, teamwork, and conflict resolution.The main goal of the article is to define coaching as a method of personnel management and consider the main types of coaching, such as corporate, business, and life coaching. The article also considers the comparative characteristics of coaching with other methods, such as mentoring, counseling, and training, which allows the differences and advantages of the coaching approach to be clearly defined. Coaching differs from traditional methods in that it contributes not only to training new skills but also to developing employees' internal potential, motivation, and ability to make independent decisions. The authors emphasize the importance of using coaching as a tool for achieving efficiency at the level of individual employees and within the company. In particular, the authors consider the practical application of coaching in Ukrainian enterprises, where this method is just beginning to be implemented, but already demonstrates positive results in improving productivity and the internal atmosphere in organizations.During the analysis, it was also noted that coaching is an effective tool for improving corporate culture and leadership development. An important aspect is that coaching requires certain knowledge and skills from managers, so the effectiveness of this method directly depends on the willingness of managers to invest in staff development and introduce new management approaches.The conclusions of the article confirm that coaching is a powerful tool for improving the efficiency of personnel management and organizational development, contributing to improved communication, motivation, and a healthier work environment. However, successful implementation of coaching in Ukraine requires constant support from the management, as well as adaptation of this method to the specifics of the domestic labor market.Thus, coaching, as a method of personnel development, has great potential to contribute to the success of both individual employees and entire companies, ensuring their adaptation to changes and increasing their competitiveness in the market.
Keywords: personnel; personnel development; personnel management methods; coaching; types of coaching